Changes in natural head position in response to mandibular advancement. Issue 5 (June 2017) - Lin, Xiaozhen; Edwards, Sean P.
Abstract: We investigated the change in the natural head position and its relation to the change in the mandibular position in patients with mandibular hypoplasia. Forty-one patients treated by orthognathic surgery were divided into three groups: bilateral sagittal split osteotomy (BSSO) advancement (n = 8); BSSO advancement with genioplasty (n = 12), and Le Fort I osteotomy with BSSO advancement (n = 21). Cone-beam computed tomographic (CT) datasets were collected preoperatively and six weeks postoperatively. The natural head position was measured using the craniocervical angle and the distance from the second vertebra to the frontal plane, and the mandibular position was measured using the craniomandibular angle and the distance from the mandible to the frontal plane. Repeated measures two way ANOVA was used to assess the significance of differences between the angular and linear measurements, and Pearson's correlation coefficient to assess those between the change in the mandibular position and the natural head position. The craniomandibular angle increased and the mandible to frontal plane distance decreased, as planned; the craniocervical angle increased, and the distance from the second vertebra to the frontal plane decreased in all three groups. ANOVA showed a significant difference in the time factor (preoperative compared with postoperative) but no significant differences between the groups or interaction (time multiplied by group) factors. There was a significant correlation between the change in mandibular position and the change in the natural head position. Changes in the natural head position after correction of mandibular hypoplasia are correlated with the change in the mandibular position, regardless of whether a genioplasty or Le Fort I osteotomy was done.